Influência da levedura e derivados sobre o desempenho e sobrevivência de juvenis do camarão Macrobrachium amazonicum - Hisano, Hamilton; Falcon, Dario Rocha; Barros, Margarida Maria; Pezzato, Luiz Edivaldo (Ciência Animal Brasileira / Brazilian Animal Science, 2008)
Supplements of whole yeast spray dried Saccharomyces cerevisiae and yeast derivatives (autolyzed yeast, mannanoligosaccharide and β-glucan) in to diets fed to juvenile Amazon River prawn were evaluated. Prawns with initial weight (1.27 ± 0.07 g) and initial length (5.49 ± 0.09 cm) were stocked in to 200 L aquaria (10 prawns/aquarium), in flow-through water system with controlled temperature, during 60 days. The experimental design was completely randomized with five treatments and four replicates. The diets were formulated to be isoproteic (35.0% CP) and isoenergetic (3500 kcal/kg GE) supplemented with no yeast and yeast derivatives - control, whole yeast - 2.0%, autolyzed yeast - 2.0%, mannanoligosaccharide - 0.2% and β-glucan - 0.2%. Weight gain of prawns fed diet containing mannanoligosaccharide yeast derivative was significantly (P<0.05) higher than prawns fed the others diets. The results indicate that 0.2% of mannanoligosaccharide supplementation provided better growth responses of juvenile M. amazonicum. KEYWORDS: aquaculture, Amazon River prawn, glucan, mannan.